LGBTQ digital cultures a global perspective - Pain, Paromita (New York Routledge Taylor & Francis Group, 2022)
"Emphasizing an intersectional and transnational approach, this collection examines how social media and digital technologies have impacted the sphere of LGBTQ activism, advocacy, education, empowerment, identity, protest, and self-expression. This edited collection adopts a critical and cultural studies perspective to examine queer cyberculture and presence. Through the lens of representation and identity politics, it explores topics such as race, disability, and colonialism, alongside sexuality and gender. The collection examines how digital technologies have made queer cultural production more expansive and how such technological affordances and platforms have enabled queer cultural practices to be more transformational. Bringing together contributors and case studies from different countries, the contributions grapple with the tensions that arise when visibility, hiddenness, renditions of the self and collective contractions of identity must be negotiated in a variety of global contexts and explores this influence on contemporary political identities. This book provides an essential introduction to LGBTQ digital cultures for students, researchers and scholars of media, communication and cultural studies. It will also be of interest to activists wanting to learn more about the transformative potential of digital media and technology in LGBTQ advocacy and empowerment around the globe"--
Includes bibliographical references and index.
Keywords: Gay people in mass media; Gay rights; Mass media and gay people; Gay people -- Political activity